The Effect of Different Processing Techniques of Beefsteak with Eel (Monopterus Albus) Raw Materials - Adi, Catur Pramono; Panjaitan, Pola S.T.; Marleni, Novita Rizki; Soeprijadi, Liliek (PELAGICUS, 2023)
One of the techniques commonly used to produce beefsteak is high temperature processing techniques. Research purposes; making eel steaks with different concentrations of eel meat, knowing the effect of processing techniques by grilling and steaming on eel steaks, testing the sensory quality, chemical quality and microbiological quality of eel steaks. The selection of eel raw materials is intended to utilize eel which contains high nutritional value and to increase its added value. The results of the research show that the organoleptic test results for fresh eel are so that the raw material can be said to be suitable. The results of the hedonic test for the highest appearance were sample C with a value of 6.81; The highest aroma value in sample C was 6.71; the highest taste score is D with a score of 6.76; and the texture got the highest score in sample C with a score of 6.71. It can be seen that sample C has a superior value in the hedonic test. The highest protein chemical test results were in sample C at 11.85%, the highest fat content in sample C was 3.33%, the lowest ash content in sample A was 2.39%, and the highest water content in sample A was 60.76%. It can be seen that the chemical tests that have sufficient nutritional value are samples C and A. Meanwhile, vitamin A has a good value for the steaming processing technique, namely 0.38.